Facts about Vitamin E - Jennifer Hillan (EDIS)
Revised! FCS-8641, a 2-page fact sheet by Jennifer Hillan, has been updated with new graphics and updated recommendations concerning vitamin E supplements and interactions with other drugs. Published by the UF Department of Family Youth and Community Sciences, April 2006.